Human Rights and Social Justice in Qur’anic Exegesis: A Thematic and Hermeneutical Study - Pujiono; Muslim Fikri; Naqiyah (Lembaga Bale Literasi, 2026)
Human rights and social justice remain central issues in contemporary global discourse, often perceived as products of Western modernity. This perception has contributed to ongoing debates regarding their compatibility with religious traditions, particularly Islam. This study examines the Qur’anic foundations of human rights and social justice through a thematic and hermeneutical analysis of classical and contemporary tafsir literature. Employing qualitative library-based research and a tafs?r mawd?‘? approach, the study analyzes key Qur’anic concepts such as the right to life, human dignity, equality, freedom, justice, distributive responsibility, and ecological balance. The findings demonstrate that the Qur’an articulates a comprehensive ethical framework for human rights grounded in divine authority and universal human dignity. Classical exegetes emphasize the normative and legal dimensions of justice, while modern interpreters expand Qur’anic ethics to address pluralism, constitutionalism, welfare state principles, religious moderation, sustainability, and education. Rather than contradicting universal human rights, the Qur’anic worldview provides a moral and spiritual foundation that reinforces justice, inclusivity, and social responsibility. This study contributes to Qur’anic studies and human rights scholarship by highlighting the relevance of Islamic ethical principles in contemporary legal, social, and global sustainability debates. It affirms that Qur’anic interpretation can serve as a constructive partner in advancing an inclusive and equitable human rights discourse.